Contributing Factors to Teachers’ Perceived Readiness for Changes Implemented in General Secondary and Preparatory Schools of Awi Zone - Kassa, Temesgen Melaku; Wondmie, Molla Bekele (Bahir Dar Journal of Education, 2020)
This study examined the perceived readiness of teachers for changes implemented in preparatory and secondary schools of the Awi zone. It also attempted to determine the factors contributing to teachers’ perceived readiness for implementing the changes. To meet these two purposes a correlational design was employed. Data were collected from 242 randomly selected preparatory and secondary school teachers. Both descriptive and inferential statistics were used to analyze the data. The results revealed that the mean scores of teachers’ readiness for change, the process factors, and the context factors were significantly higher than the respective test values at p